HIDROQUÍMICA DE MASSAS D’ÁGUA OCEÂNICAS EM REGIÕES DA MARGEM CONTINENTAL BRASILEIRA, BACIA DE CAMPOS, ESTADO DO RIO DE JANEIRO, BRASIL - Pedrosa, Paulo; Paranhos, Rodolfo; Suzuki, Marina Satika; Andrade, Luciana; da Silveira, Ilson Carlos A.; Schmidt, André Campos Kersten; Falcão, Ana Paula; Lavrado, Helena Passeri; Rezende, Carlos Eduardo (Geochimica Brasiliensis, 2012)